Vitaceae - A new and an overlooked record of Cyphostemma in Angola - F. De Sousa; E. Figueiredo; G. F. Smith (Bothalia: African Biodiversity & Conservation, 2011)
A new and an overlooked record of Cyphostemma in Angola.